GARRANTIES OF THE RIGHT OF CITIZENS TO APPLY - Mavlonov Feruz Oblakulovich (Web of Journals Publishing, 2023)
In the research work, the concept of appeals of individuals and legal entities, organizational and legal issues that arise in the process of working with appeals, mechanisms of their implementation, existing legal relations related to the effective organization of appeals of individuals and legal entities are analyzed. In this research work, the opinions of foreign scientists about the concept and essence of appeals are systematically analyzed.
Keywords: application, citizen, society, state, state body, law, application, public service, law